Analisis Perubahan Posisi Bagan Tancap dengan Citra Google Earth Tahun 2007, 2013, 2018 Laut Palopo - Feri padli (Universitas Negeri Makassar, 2022)
Recent advances in remote-sensing technology allow us to control the position change in certain period. By using Google Earth Imagery, the position change of stationary lift net can be seen in a period of 10 years, starting from 2007 to 2018. Furthermore, mapping the position change of the stationary lift net by ArcGIS application and counting the ratio number of change in stationary lift net from 2007 to 2018. The method used in this research is to interpret the position change by using Google Earth Imagery, field survey and interview with local society to find general description of stationary lift net. The data analyzed by using spatial analysis that consist of detection, identification, and analyzing the position change of stationary lift net by Google Earth Imagery. The result indicated the position of stationary lift net experience the position changes every 5 years. In 2007 to 2013 stationary lift net pattern is extending from north to south while in 2013 to 2018 the pattern spreading. The number of stationary lift net has decreased from 55 to 36 in 10 years, however the changes pattern tends to be constantly